IDDF2018-ABS-0114 SOF/VEL/VOX results in high SVR12 rates when administered for 12 weeks in DAA-experienced patients or for 8 weeks in daa-naive patients: an integrated analysis of the polaris-1, polaris-2, polaris-3 and polaris-4 studies. (June 2018) - Roberts, Stuart K; Cooper, Curtis L; Lawitz, Eric; Rajender Reddy, K; Thompson, Alex J; Zeuzem, Stefan; Jacobson, Ira M; Ruane, Peter; Hyland, Robert H; Stamm, Luisa M; Han, Lingling; Brainard, Diana M; et al.
Abstract : Background: The once-daily fixed-dose combination tablet of sofosbuvir/velpatasvir/voxilaprevir(SOF/VEL/VOX) was evaluated for the treatment of genotype 1–6 HCV infection in four Phase 3 studies in direct-acting antiviral (DAA)-experienced (POLARIS-1 and POLARIS-4) and DAA-naive (POLARIS-2 and POLARIS-3) patients with and without compensated cirrhosis. DAA-experienced patients received treatment for 12 weeks, and DAA-naive patients received treatment for 8 weeks. Overall SVR12 rates were >95% across all the studies. This post-hoc analysis assesses efficacy in patients with and without traditional negative predictors of response. Methods: This was a retrospective analysis of data from 1056 patients treated with SOF/VEL/VOX in the Phase 3 studies. Presence of cirrhosis was determined by histology, Fibrotest/APRI, or Fibroscan. Viral load and other clinical and laboratory assessments were determined prior to treatment with SOF/VEL/VOX. Prior treatment records were source verified, and race was self-reported by the patient to the investigator. Results: Overall, 38% of patients had cirrhosis, 70% had HCV RNA ≥800, 000 IU/mL, 59% of the DAA-experienced patients had received an NS5A inhibitor-containing regimen, 20% of the DAA-naive patients had prior treatment failure with pegylated interferon +ribavirin, 12% were ≥65 years old and 10% were black. Conclusions: The POLARIS-1, POLARIS-2, POLARIS-3, and POLARIS-4 studies enrolled a diverse patient population that included a significant number of patients with historically negative predictors of response including cirrhosis and prior exposure to DAA-containing regimens. High SVR12 rates for the ribavirin-free regimen of SOF/VEL/VOX were achieved across subgroups.